Review of Design Freedom Offered by Additive Manufacturing for Performance Enhancement of Electrical Machine - Zahoor Ahmad; Ants Kallaste; Toomas Vaimann; Muhammad Usman Naseer; Shahid Hussain; Anton Rassolkin (IEEE Open Journal of the Industrial Electronics Society)
Additive manufacturing (AM) enables the creation of parts with exceptional geometric versatility, creating new possibilities for developing nonsymmetrical electrical machines (EM) with compact structures, reduced mass density, high torque, better power density, and minimal material waste during fabrication. This review highlights the current state of AM methods and their critical role in the production of EM. The impact of the additively built EM components concerning performance indices, including torque, power density, and efficiency, is highlighted. In addition, an overview of the constraints associated with the traditional production process of EM-specific components and the role of AM in addressing those limitations is emphasized. As per the current state of AM in the context of EM production, the nonconventional structures of the stator and rotor core of EMs are feasible to fabricate to accomplish improved utilization of magnetic flux. Moreover, AM enables the fabrication of windings/coils of any profiles with integrated functionality, including the design of thermal management mechanisms to enhance EM performance and achieve thermally controlled EM. However, the current state of AM technology is not very advanced and requires additional improvement, particularly in areas of EM production, which are minimizing eddy current losses, high-quality surface refinement, build volume restrictions, and simultaneous multimaterials processing.